SPE Annual Technical Conference and Exhibition 2008
DOI: 10.2118/116731-ms
|View full text |Cite
|
Sign up to set email alerts
|

Exponential vs. Hyperbolic Decline in Tight Gas Sands — Understanding the Origin and Implications for Reserve Estimates Using Arps' Decline Curves

Abstract: When tight gas sand reserves are assessed using the Arps rate-time equations, the decline behavior is typically defined in terms of the Arps decline exponent, b. The original Arps paper indicated that the b-exponent should lie between 0 and 1.0 on a semilog plot. However, in practice we often observe values much greater than 1.0, especially prior to the onset of true boundary-dominated flow. Unfortunately, the correct b-exponent is difficult (if not impossible) to identify during the early decline period — and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
179
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(191 citation statements)
references
References 13 publications
2
179
1
1
Order By: Relevance
“…It has been claimed that the Arps decline curves encounter problems when used in "unconventional" formations, particularly with regards to overestimation of reserves. When traditional Unit: bcf per day decline curve models are used on shale formations, Arps' values for larger than 1 are commonly obtained yielding infinite cumulative production [24]. As the importance of shale gas has increased over the last decade new methods have been proposed to model the behavior exhibited by long horizontal wells with multistage hydraulic fractures in shale reservoirs.…”
Section: Decline Curve Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been claimed that the Arps decline curves encounter problems when used in "unconventional" formations, particularly with regards to overestimation of reserves. When traditional Unit: bcf per day decline curve models are used on shale formations, Arps' values for larger than 1 are commonly obtained yielding infinite cumulative production [24]. As the importance of shale gas has increased over the last decade new methods have been proposed to model the behavior exhibited by long horizontal wells with multistage hydraulic fractures in shale reservoirs.…”
Section: Decline Curve Modelsmentioning
confidence: 99%
“…As the importance of shale gas has increased over the last decade new methods have been proposed to model the behavior exhibited by long horizontal wells with multistage hydraulic fractures in shale reservoirs. These methods include, but are not limited to, the Stretched Exponential (SE) model [25,26], the Power Law model [24], and Duong's model [27]. Two decline curve analysis models are used in the study -the Arps Hyperbolic model and the Stretched Exponential model.…”
Section: Decline Curve Modelsmentioning
confidence: 99%
“…1 that returned a b value [1 is a consequence of flow that is still dominated by transient effects. Several authors (Can and Kabir 2014;Ilk et al 2008;Rushing et al 2007) have pointed out that Eqs. 1 and 2 will yield optimistic results when applied to unconventional formations.…”
Section: Introductionmentioning
confidence: 99%
“…Clark et al (2011) introduced the logistic growth model, which has the desirable property of yielding physical values of reserves recovery. Ilk (2010), after analyzing production (rate) data from shale gas wells, developed a power-law model and a method of applying the model that arbitrarily switched from the power-law decline behavior to an exponential decline behavior. Duong (2011) also observed that a loglog plot of q/N p versus time was a straight line.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, several empirical decline curve analysis (DCA) models have been used to forecast reservoir production such as the Arps' hyperbolic decline model [1], Duong's model [2], the Stretched Exponential Production Decline (SEPD) model [3], the power-law model [4] and more recently the YM-SEPD model [5]. All these models have limitations, which have made them not entirely satisfactory for forecasting production from unconventional reservoirs, especially when production history is short.…”
Section: Introductionmentioning
confidence: 99%